Municipal water fluoridation, adolescent IQ, and cognition across the life course: Evidence from the Wisconsin Longitudinal Study - John Robert Warren; Gina Rumore; Kamil Sicinski; Pamela Herd; Michal Engelman (Proceedings of the National Academy of Sciences, 2026)
We investigate associations between community water fluoridation (CWF), adolescent IQ, and cognition across the life course using representative data from the US state of Wisconsin. Exposure is inferred from historical records on community water fluoridation; adolescent IQ is ascertained from state testing records; and cognition in later life is assessed as part of the Wisconsin Longitudinal Study [P. Herd et al. , Int. J. Epidemiol. 43 , 34–41 (2014).]. In contrast to studies cited in recent decisions to end CWF in Utah, Florida, and elsewhere, we find no evidence that CWF is negatively associated with adolescent IQ or adult cognitive functioning.